The Association between Mammographic and Ultrasound Features and Histologic Grade in Invasive Ductal Carcinoma of the Breast - Voraparee Suvannarerg, M.D. (Siriraj Medical Journal, 2018)
Objective: To evaluate the relationships between mammographic and ultrasound features and histological grades of invasive ductal carcinoma using the terminology of the fifth edition of Breast Imaging Reporting and Data System (BI-RADS). Methods: Mammographic and ultrasound features of invasive breast carcinomas diagnosed in 104 consecutive women between January 2011 and August 2014 were retrospectively reviewed, described according to the BI-RADS lexicon, and correlated with histological tumor grade according to the Nottingham histologic scoring system. Results: 104 invasive ductal carcinomas were graded histologically as follows: grade 1, 12.5%; grade 2, 50%; and grade 3, 37.5%. In multivariate analyses, mammographically identified oval or round shape of masses and indistinct margin were significantly associated with grade 3 tumors (p < 0.05). In addition, ultrasound-identified microlobulated margin was significantly associated (p = 0.013) with grade 3 tumors. In contrast, mammographically identified spiculated margin and ultrasound-identified posterior shadowing occurred significantly more frequently in grade 1 tumors (p < 0.05). Conclusion: Mammographic and ultrasound features are effective predictors of histologic tumor grade of breast cancer.